1998
DOI: 10.1002/(sici)1096-8652(199806)58:2<130::aid-ajh8>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinically silent primary adrenal lymphoma: A case report and review of the literature

Abstract: Primary adrenal lymphoma (PAL) is extremely uncommon. We describe a case of clinically silent non-Hodgkin's B-cell lymphoma of diffuse large cell type with exclusive left adrenal localization. The tumor was discovered by computed tomography (CT) as a 2.5-cm dense mass and diagnosed at autopsy. Literature concerning this unusual neoplasm is reviewed. During the early stage, particularly when the lesion is small, PAL is likely to be missed. This unusual entity should be included in the differential diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 26 publications
3
53
0
5
Order By: Relevance
“…There may be low attenuation foci in the masses that may be due to necrosis [2,3], as demonstrated in our case. Recent studies demonstrated that fluorodeoxyglucose positron emission tomography has high sensitivity and specificity for differentiating malignant from benign adrenal masses [2,7]. Nevertheless, there is no pathognomonic appearance on imaging studies to indicate lymphomatous involvement of the adrenal glands [2][3][4]7].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…There may be low attenuation foci in the masses that may be due to necrosis [2,3], as demonstrated in our case. Recent studies demonstrated that fluorodeoxyglucose positron emission tomography has high sensitivity and specificity for differentiating malignant from benign adrenal masses [2,7]. Nevertheless, there is no pathognomonic appearance on imaging studies to indicate lymphomatous involvement of the adrenal glands [2][3][4]7].…”
Section: Discussionsupporting
confidence: 55%
“…CT scan is considered the most important imaging modality in evaluating adrenal masses. PAL tends to appear as complex masses with a variable density on CT scan and MRI [2,4]. A small number of PALs show homogenous density [2][3][4]7], but no calcification, fat content, or hemorrhage were observed in the masses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations